16% efficient silicon/organic heterojunction solar cells using narrow band-gap conjugated polyelectrolytes based low resistance electron-selective contacts. (January 2018) - He, Jian; Zhang, Wenjun; Ye, Jichun; Gao, Pingqi
Abstract: Dopant-free silicon (Si)/organic heterojunction solar cells (HSCs) have drawn much attention due to their immense potential in achieving high power conversion efficiencies (PCEs) with simple device architectures and fabrication procedures. However, unsatisfied rear-contacts severely hinder further improvement in PCEs for these promising HSCs. Exploring effective cathodic interfacial materials with low temperature fabrication to replace conventional diffusion layer shows the extremely importance of technical innovation. Here, poly[4, 8-bis(2-ethylhexyloxyl)benzo[1, 2-b:4, 5-b']dithiophene-2, 6-diyl- alt -ethylhexyl-3-fluorothieno[3, 4-b]thiophene-2-carboxylate-4, 6-diyl] (PTB7)-based narrow band-gap conjugated polyelectrolytes, PTB7-NBr and PTB7-NSO3, are firstly employed as effective cathodic interfacial materials in Si/organic HSCs to improve the passivation and electron transporting property at n -Si/Al interface. The low-temperature proceeded electron-selective contact of n -Si/PTB7-NBr/Al gives a contact resistivity as low as 6.7 ± 0.8 mΩ cm 2, upon it a remarkable PCE of 16.0% is finally obtained from a completely dopant-free Si/organic HSC. The understanding of conjugated polyelectrolytes on interfacial modification may lead a path to fabricate high performance Si/organic heterojunction devices with efficient charge transfer process at a simplified fabrication process. Graphical abstract: Dopant-free silicon (Si)/organic heterojunction solar cells have drawn much attention due to their immense potential in achieving high power conversion efficiencies. In this paper, Narrow band-gap conjugated polyelectrolyte, PTB7-NBr, is firstly used as cathode interlayer to improve the contact property of n -Si/Al, as well as the electron transporting property, leading to an ultralow contact resistivity of 6.7 ± 0.8 mΩ cm 2 . N -Si/PEDOT:PSS heterojunction solar cells with remarkable power conversion efficiency of 16.0% is finally achieved by employing n -Si/PTB7-NBr/Al as electron-selective contact. Highlights: Narrow band-gap conjugate polyelectrolytes are used as cathode interlayer in n -Si/PEDOT:PSS heterojunction solar cells. Contact resistivity of 6.7 ± 0.8 mΩ cm 2 is achieved when use PTB7-NBr as cathode interlayer Heterojunction solar cells with remarkable efficiency of 16% is received via a totally dopant-free fabrication procedure.